2021
DOI: 10.1001/jamanetworkopen.2020.37209
|View full text |Cite
|
Sign up to set email alerts
|

Human Health Risks of Conducted Electrical Weapon Exposure

Abstract: IMPORTANCE Conducted electrical weapons (CEWs) are used broadly as a less-lethal force option for police officers. However, there is no clear picture of the possible health risks in humans on the basis of rigorously assessed scientific evidence from the international peer-reviewed literature. OBJECTIVE To synthesize and systematically evaluate the strength of published evidence for an association between exposure to different models of CEWs and adverse acute as well as chronic conditions. EVIDENCE REVIEW Follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Studies were all experimental, largely recruiting a small sample of healthy individuals who are unlikely to represent the population exposed to Tasers. The review further found that many studies received funding from the Taser manufacturer (Baliatsas et al, 2021). The finding that there is a need for higher quality research is echoed in other reviews (Semple et al, 2021;Sheppard & Welsh, 2022).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Studies were all experimental, largely recruiting a small sample of healthy individuals who are unlikely to represent the population exposed to Tasers. The review further found that many studies received funding from the Taser manufacturer (Baliatsas et al, 2021). The finding that there is a need for higher quality research is echoed in other reviews (Semple et al, 2021;Sheppard & Welsh, 2022).…”
Section: Introductionmentioning
confidence: 94%
“…A 2021 systematic review on the health risks of Tasers found that the risk of adverse outcomes due to use is low (Baliatsas et al, 2021). However, the review also identified methodological and quality issues with most studies.…”
Section: Introductionmentioning
confidence: 99%
“… Ho et al (2011) found that simply using the laser sighting device, which projects red dots on the individual, prevented interactions with agitated patients from escalating. Ideally, officers should also know what intervention options work best in any given set of circumstances, with respect to both effectiveness and safety ( Baldwin et al, 2018 ; Baliatsas et al, 2021 ; Semple et al, 2021a ).…”
Section: Officer Ksas Identified In the Literaturementioning
confidence: 99%
“…For two decades, researchers have explored the physiological effects of the use of TASER ® 1 technology and its relationship to adverse reactions and sudden arrest-related deaths (Kroll, 2009; Vilke et al, 2007; Williams, 2008; Webster et al, 2006; Werner et al, 2012). Physiological research has examined cardiac, respiratory, and metabolic effects (Baliatsas et al, 2021; Bozeman et al, 2009; Jauchem et al, 2009). More recently, research has centered on the effects of associated trauma, such as injuries from uncontrolled falls, from the ignition of volatile fumes, and from impacts to the eyes (Gapsis et al, 2017; Kroll et al, 2016; Kroll et al, 2017).…”
Section: Introductionmentioning
confidence: 99%